2009
DOI: 10.33776/amc.v35i152.1224
|View full text |Cite
|
Sign up to set email alerts
|

Roles de género y salud de mujeres y hombres

Abstract: Roles de género y salud de mujeres y hombres Este trabajo ha sido realizado a través del proyecto de investigación PSI2008-02543/PSIC, subvencionado

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
0
0
1
Order By: Relevance
“…Conversely, no significant data were obtained to explain the relation of gender roles with stress, anxiety, or depression. Similar to our study, a study performed in 2009 in Spain [29] with a sample of 337 people aged 17-74 years (M = 32.2 years, SD = 12.2), with different socio-demographic and genderdifferentiated characteristics, found that women obtained higher mean scores for somatic symptoms, anxiety, and insomnia than men. The same study observed associations between gender roles and mental health (anxiety, insomnia, depression).…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, no significant data were obtained to explain the relation of gender roles with stress, anxiety, or depression. Similar to our study, a study performed in 2009 in Spain [29] with a sample of 337 people aged 17-74 years (M = 32.2 years, SD = 12.2), with different socio-demographic and genderdifferentiated characteristics, found that women obtained higher mean scores for somatic symptoms, anxiety, and insomnia than men. The same study observed associations between gender roles and mental health (anxiety, insomnia, depression).…”
Section: Discussionsupporting
confidence: 89%
“…Su finalidad es dicotomizar las características para seguir manteniendo la dominación de los hombres y la subordinación de las mujeres (Velandia-Morales y Rincón, 2014). Se trata de asociaciones prejuiciosas que la sociedad normaliza, siendo las tareas y características asignadas a las mujeres las más negativas y menos valoradas, a pesar de que la ciencia no ha aportado ninguna evidencia empírica sobre la existencia de una distinción natural entre hombres y mujeres (Matud et al, 2010).…”
Section: Métodos Y Fundamentación Teóricaunclassified